Base Nacional Comum Curricular para a educação infantil: entre desafios e possibilidades dos campos de experiência educativa - Luciane Pandini-Simiano; Márcia Buss-Simão (EccoS – Revista Científica)
Abstract : This text has the intention to contribute to the discussion of national curriculum basis, focusing on the challenges and opportunities of the Common National Curriculum Basis of Basic Education for early childhood education from the proposal of Experience Fields. For this, it is organized into three parts, the first, from the Brazilian educational legislation, presents a set of guidance documents that support the educational politics in early childhood education and highlight the right of children to education. In the second time discusses the Common National Curriculum basis for early childhood education and its organization proposal from Experience Fields. In sequence concludes pointing the possibilities and challenges of experience fields in early childhood education.